2015
DOI: 10.1523/jneurosci.0003-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Elicits Functional and Structural Plasticity Selectively in Dopamine D1 Receptor-Expressing Neurons of the Dorsomedial Striatum

Abstract: Addiction is thought to be a maladaptive form of learning and memory caused by drug-evoked aberrant synaptic plasticity. We previously showed that alcohol facilitates synaptic plasticity in the dorsomedial striatum (DMS), a brain region that drives goal-directed behaviors. The majority of DMS cells are medium spiny neurons (MSNs) that express dopamine D1 receptors (D1Rs) or D2 receptors (D2Rs), which drive "Go" or "No-Go" behaviors, respectively. Here, we report that alcohol induces cell type-specific synaptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
117
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(136 citation statements)
references
References 58 publications
18
117
1
Order By: Relevance
“…In support of these findings are previous studies that have suggested a role of kainate, but not AMPA, receptors in mediating the reinforcing properties of alcohol (Stephens and Brown, 1999;Czachowski et al, 2012;Wang et al, 2012). However, our findings may be surprising in light of previous reports showing that pharmacological blockade of NMDARs decreases operant self-administration in rats (Sabino et al, 2013;Jeanblanc et al, 2014;Alaux-Cantin et al, 2015; but see also Piasecki et al, 1998).…”
Section: D1creert2supporting
confidence: 78%
See 1 more Smart Citation
“…In support of these findings are previous studies that have suggested a role of kainate, but not AMPA, receptors in mediating the reinforcing properties of alcohol (Stephens and Brown, 1999;Czachowski et al, 2012;Wang et al, 2012). However, our findings may be surprising in light of previous reports showing that pharmacological blockade of NMDARs decreases operant self-administration in rats (Sabino et al, 2013;Jeanblanc et al, 2014;Alaux-Cantin et al, 2015; but see also Piasecki et al, 1998).…”
Section: D1creert2supporting
confidence: 78%
“…Although there is growing evidence that D2-expressing MSNs mediate several effects induced by alcohol , in a recent report by Wang et al 2015)) it was demonstrated that alcohol consumption induces a long-lasting increase in AMPAR activity specifically in D1-MSNs, but not in D2-MSNs, and striatal blockade of D1R, but not D2R, activity attenuates alcohol consumption. Therefore, we studied the contribution of NMDARs and AMPARs onto D1-MSNs in mediating addictivelike behavior.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, we previously showed that excessive alcohol drinking increases dendritic branch length in D1R MSNs in the DMS (Wang et al, 2015), a change that we did not observe in the NAc shell of alcohol-drinking mice. In addition, and in contrast to the data presented herein, Uys et al recently reported that chronic exposure to alcohol vapor increases the number of thin, stubby, and filopodia spines in the NAc core, and that 72 hours of withdrawal from CIE produced a reduction in the number of mushroom-type spines (Uys et al, 2016).…”
Section: Discussioncontrasting
confidence: 61%
“…Image z stacks of between 15 and 20 images were acquired at a z separation of 0.3 μm. Images of spines were deconvoluted by AutoQuant X3 (Media Cybernetics) (Wang et al, 2015), and morphological properties were analyzed by using FIJI software (NIH) (Smith et al, 2009). Protrusions from dendrites were classified into 4 types based on their length and neck and head morphology (Hering and Sheng, 2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation